Mobility of Nitrogen in the Soil Due to the Use of Organomineral Fertilizers with Different Concentrations of Phosphorus - Grohskopf, Marco Andre [UNESP]; Correa, Juliano Corulli; Fernandes, Dirceu Maximino [UNESP]; Teixeira, Paulo Cesar; Almeida Mota, Sandra Camile (Taylor & Francis Inc, 2019)
The inorganic nitrogen mobility as a response to the use of organomineral fertilizers in interaction with the phosphorus is altered around the granules in variable charge soils. The aim of this research was to evaluate the inorganic N mobility in a Typic Hapludox as a response to the interaction with P in organomineral fertilizers. The experiment in Petri dishes was carried out in a completely randomized design, with six repetitions. The treatments comprised eight P concentrations (0; 1.3; 1.8; 2.5; 3.5; 5 and 10 mg/dish) in the organomineral, besides the control (unfertilized) and urea, with the N dose fixed in 5 mg/dish. In the Petri dishes, the granules of fertilizers were placed in the center, and posteriorly, placed in incubation for 7, 14, 21, 28 and 35 days, being in each time, sampled concentric rings of soil in four distances from the central point (0 - 7.75; 7.76 - 13.5; 13.51 - 25.5; and 25.51 - 43 mm). The concentration of P in the organomineral and the amount applied interfered in the mobility of ammonia and nitrate in the soil around the fertilizer granules. Until 21 days there was predominance of nitrogen in the ammonia form with displacement until section 2 (7.76 - 13.5 mm), whereas the form of nitrate had higher proportion after 28 days with mobility until section 4 (25.51 - 43 mm). The smallest concentrations of P in the organomineral demonstrated the largest contents of nitrate, whereas the largest concentrations of P kept the ammonia longer in the soil.
Keywords: Poultry litter; N; P ratio; displacement; mineral nitrogen